Rotor core, its manufacturing method and motor

By employing laser cutting with controlled angles and alloy compositions, the rotor core's fatigue strength and manufacturability are improved, addressing productivity and cost issues in high-speed motor production.

JP7601068B2Active Publication Date: 2024-12-17JFE STEEL CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022138304
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-09-10
Filing Date
2022-08-31
Publication Date
2024-12-17
Estimated Expiration
2042-08-31

AI Technical Summary

Technical Problem

Existing methods for improving the fatigue strength and manufacturability of rotor cores in high-speed motors, such as IPM motors, face challenges related to productivity, cost, and motor characteristics, with conventional techniques either being inefficient or requiring strict control of annealing conditions, leading to suboptimal results.

Method used

The rotor core is manufactured using thermal cutting, specifically laser cutting, to reduce the step difference at grain boundaries to 0.5 μm or less, optimizing the cutting process by adjusting the laser beam angle to 1 to 5 degrees, and using a non-oriented electrical steel sheet with controlled Si and other alloy compositions.

Benefits of technology

This approach enhances the rotor core's fatigue strength and reliability while allowing for better air gap control, improving motor efficiency and reducing manufacturing complexity and costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601068000004
    Figure 0007601068000004
  • Figure 0007601068000005
    Figure 0007601068000005
  • Figure 0007601068000006
    Figure 0007601068000006
Patent Text Reader

Abstract

To provide a rotor core excellent in strength characteristics, especially fatigue characteristics, to propose a manufacturing method thereof, and to provide a motor which facilitates control of an air gap using the rotor core.SOLUTION: After a plurality of holes is formed in the rotor core shaped steel plate taken from the raw steel plate having a predetermined component composition by heat cutting processing, the rotor core is manufactured by setting a maximum value of a step at the crystal grain boundary existing on the cut surface to be 0.5 μm or less and by irradiating the hole side cut off with respect to a normal line of the surface of the steel plate with heat beams at an angle of 1 to 5° in heat cutting process when the rotor core is manufactured by laminating the steel plates. Moreover, disclosed is a motor whose shortest distance between the inner diameters of the rotor core and a stator core is equal to or smaller than 0.30 mm.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rotor core used in a high-speed motor such as a drive motor for an electric vehicle, a manufacturing method thereof, and a motor using the rotor core. [Background technology]

[0002] The drive motors used in electric vehicles are driven in the high frequency range in order to reduce size and increase efficiency. Interior permanent magnet motors (IPM motors), which have permanent magnets embedded inside the rotor core, are often used for such motors.

[0003] When the IPM motor rotates at high speed, a large centrifugal force acts on the magnets embedded in the rotor core, tending to jump out in the radial direction of the rotor. Furthermore, as the motor's rotation speed changes significantly with the acceleration and deceleration of the vehicle, the centrifugal force acting on the magnets also changes constantly. For this reason, the rotor core is required to have not only excellent magnetic properties, but also excellent strength properties such as tensile strength and fatigue strength.

[0004] In response to the above demands, improvements in strength properties have been made mainly from the perspective of materials, such as by adding large amounts of elements such as Si and Al, or by controlling the crystal grain size and crystal orientation. However, improving strength properties by adding such alloying elements makes the steel sheets that make up the rotor core hard and brittle, which has a negative effect on the manufacturability of the steel sheets themselves. In addition, a method of improving strength properties by reducing the crystal grain size can achieve a certain degree of effect by lowering the finish annealing temperature. However, strict control of annealing conditions is required to stably obtain fine recrystallized grains of several tens of μm or less, and in some cases, the processed structure remains in the structure, which results in a problem that the magnetic properties and strength properties are not improved as much as expected. As described above, there was a limit to improving strength properties from the perspective of the materials (steel sheets) that make up the rotor core.

[0005] In the manufacturing process of motor cores, punching is generally used to cut a core-shaped steel sheet from a base steel sheet, but this punching process tends to have a large roughness on the cut surface, and it is known that the fatigue properties of the material after punching are inferior to those of the original material.

[0006] In response to this problem, for example, Patent Document 1 proposes a technique for improving the fatigue properties of a rotor core by chemically dissolving the end faces of holes formed by punching or the like. Patent Document 2 proposes a technique for obtaining a high-strength rotor by applying "laser peening," which irradiates a laser through a liquid onto the bridge side of the inner peripheral surface of the magnet insertion hole of the rotor core. Furthermore, Patent Document 3 proposes a method of performing a shaving process to shear and remove the plastic strain area generated by punching, and Patent Document 4 proposes a method of improving the fatigue strength of a rotor core by performing a coining process on the fracture surface of the punched end face to form a crushed surface. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2009-219306 A [Patent Document 2] JP 2005-124386 A [Patent Document 3] International Publication No. 2011 / 129000 [Patent Document 4] International Publication No. 2018 / 012599 Summary of the Invention [Problem to be solved by the invention]

[0008] However, the method disclosed in the above Patent Document 1 has problems in terms of productivity and cost, since holes are formed once by a method other than chemical dissolution, and then the end of the hole is treated by chemical dissolution. Furthermore, the dissolution rate of the chemical dissolution treatment differs depending on the orientation difference of the crystal grains at the end face. Therefore, a step is generated at the position of the crystal grain boundary at the end face (hereinafter, this step is also referred to as "step at the crystal grain boundary"), and stress is concentrated at this part, so that the effect of improving fatigue properties cannot be sufficiently obtained. In addition, the method of performing laser peening disclosed in Patent Document 2 has a problem of poor productivity. In addition, when the electromagnetic steel sheet is melted across the laminations by laser irradiation, a short circuit occurs at the melted end face, which increases eddy current loss and reduces motor efficiency. In addition, the technology of arranging the cut surface of the steel sheet processed into the core shape by post-treatment disclosed in Patent Documents 3 and 4 can improve fatigue strength, but it is difficult to strictly control the dimensional accuracy of the core and to control the air gap, which is a design factor that greatly affects the characteristics of the motor. Therefore, there is a problem that the variation in motor characteristics becomes large, and it is not an optimal method for obtaining a rotor core with excellent fatigue strength. In addition, the techniques disclosed in the above Patent Documents 3 and 4 manufacture rotor cores by mechanical processing of raw steel plates, so in the case of high-strength steel plates, there are problems such as severe wear of the mold and quality control. As described above, even when improving the strength characteristics of the rotor core from the viewpoint of the motor manufacturing process, many problems remain in terms of motor characteristics, productivity, and cost.

[0009] The present invention has been made in consideration of the above-mentioned problems associated with the conventional technology, and its object is to provide a rotor core having excellent strength characteristics, particularly fatigue characteristics, to propose a manufacturing method thereof, and to provide a motor that uses the above-mentioned rotor core to facilitate control of the air gap. [Means for solving the problem]

[0010] In order to solve the above problems, the inventors have noticed that in a steel plate processed into a rotor shape (hereinafter also referred to as a "rotor core material"), the part where stress concentration due to centrifugal force is greatest is the bridge part of the rotor core (the part sandwiched between holes for embedding magnets). They have then conducted extensive research into ways to improve the fatigue properties of the bridge part. As a result, it is effective not only to smooth the cut surface of the steel plate at the bridge part, i.e., the cut surface of the hole for embedding the magnet, but also to reduce the step existing on the cut surface at the position of the grain boundary to 0.5 μm or less. In addition, they have found that in order to achieve this, it is necessary to form the holes by thermal cutting and to optimize the heat beam irradiation conditions of the thermal cutting, which has led to the development of the present invention.

[0011] The present invention, based on the above findings, is a rotor core constructed by stacking steel plates which are extracted from raw steel plates and processed into the outer peripheral shape of the rotor core, wherein the steel plates have a plurality of holes formed by thermal cutting, and the maximum value of the step at the grain boundaries present on the cut surfaces of the holes is 0.5 μm or less.

[0012] The material steel sheet in the rotor core of the present invention is characterized in that it is a non-oriented electrical steel sheet containing C: 0.0005 to 0.01 mass%, Si: 7 mass% or less, Mn: 0.05 to 3 mass%, Al: 3 mass% or less, and optionally containing at least one selected from P: 0.001 to 0.1 mass%, S: 0.01 mass% or less, Sn: 0.001 to 0.1 mass%, Sb: 0.001 to 0.1 mass%, Ca: 0.0002 to 0.005 mass%, and Mg: 0.0002 to 0.005%, with the balance being Fe and unavoidable impurities.

[0013] In addition, the material steel plate in the rotor core of the present invention is characterized in that, when the surface layer portion is from the front and back surfaces of the steel plate to 1 / 3 of the plate thickness, and the center portion is from the surface of the steel plate to the inside of 1 / 3 of the plate thickness, the average Si content of the front and back surfaces of the surface layer portion is 1 mass% or more higher than that of the center portion.

[0014] The rotor core of the present invention is characterized in that the thermal cutting is laser cutting.

[0015] The rotor core of the present invention is characterized in that the outer periphery of a steel plate processed into the shape of the rotor core is thermally cut.

[0016] The rotor core of the present invention is characterized in that the thermal cutting of the outer periphery is laser cutting.

[0017] The rotor core of the present invention is characterized in that permanent magnets are inserted into some or all of the holes.

[0018] The present invention also proposes a method for manufacturing a rotor core, which comprises forming a plurality of holes by thermal cutting in a rotor-core-shaped steel plate taken from a base steel plate having the above-described component composition, and then stacking the steel plates to assemble a rotor core, characterized in that in the thermal cutting, a heat beam is irradiated at an angle of 1 to 5° toward the hole side to be cut off with respect to a perpendicular line to the steel plate surface, thereby making the maximum step value at the grain boundaries present on the cut surface 0.5 μm or less.

[0019] The material steel plate used in the manufacturing method of the rotor core of the present invention is characterized in that, when the surface layer portion is from the front and back surfaces of the steel plate to 1 / 3 of the plate thickness, and the center portion is from the surface of the steel plate to the inside of 1 / 3 of the plate thickness, the average Si content of the front and back surfaces of the surface layer portion is 1 mass% or more higher than that of the center portion.

[0020] In addition, the manufacturing method of the rotor core of the present invention is characterized in that the thermal cutting process is a laser cutting process.

[0021] The manufacturing method of the rotor core of the present invention is characterized in that the outer periphery of a steel plate processed into the shape of the rotor core is thermally cut.

[0022] In addition, the manufacturing method of the rotor core of the present invention is characterized in that the thermal cutting of the outer periphery is laser cutting.

[0023] The present invention also provides a motor having a rotor core and a stator core, the rotor core being formed using any of the cores described above, wherein the shortest distance between the outer diameter of the rotor core and the inner diameter of the stator core is 0.30 mm or less. Effect of the Invention

[0024] According to the present invention, it is possible to provide a rotor core with excellent fatigue characteristics without excessively restricting the freedom of design of the air gap, thereby making it possible to not only increase the efficiency of the motor but also greatly improve the reliability of the motor. [Brief description of the drawings]

[0025] [Figure 1] FIG. 2 is a diagram showing an example of a shape of a steel plate constituting a rotor core. [Diagram 2] FIG. 2 is a diagram illustrating an inclination angle θ in laser cutting processing. [Diagram 3] FIG. 2 is a diagram illustrating a fatigue test piece. [Figure 4] FIG. 1 is a diagram illustrating a method for observing a cut surface of a fatigue test piece. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] First, the rotor core for a high-speed motor that is the subject of the present invention is a rotor core to which centrifugal force is repeatedly applied. This rotor core is usually made by laminating steel plates (rotor core material) that have been processed into the outer peripheral shape of the rotor core by stamping or thermal cutting using a heat beam such as a laser beam from a raw steel plate, and assembling them by fixing them with rivets, etc. From the viewpoint of high efficiency, a plurality of permanent magnets are embedded in the rotor core of an IPM motor.

[0027] Here, in the case of a rotor core having a shape as shown in Fig. 1, it is known that the centrifugal force caused by high-speed rotation is concentrated in the bridge portion (part A or part B in Fig. 1) that is sandwiched between the holes into which the magnets are inserted (magnet insertion holes) and the holes. Therefore, such a portion is easily subject to fatigue failure due to the centrifugal force repeatedly applied.

[0028] However, since the shape of the rotor core is determined from the viewpoint of efficiency, it is difficult to change it. Therefore, as proposed in the above-mentioned Patent Documents 1 to 4, it has been considered to prevent stress concentration on the bridge portion by improving the cut surface of the magnet insertion hole. However, the above-mentioned conventional technology has much room for improvement not only in terms of the effect of improving fatigue properties, but also in terms of manufacturability.

[0029] Therefore, the inventors have conducted extensive research to solve the above problems. As a result, as described below, it has been found that in order to improve the fatigue properties of the rotor core with good productivity, it is extremely effective to form the magnet insertion holes by thermal cutting and to control the step at the grain boundary present on the cut surface by the thermal cutting to 0.5 μm or less. In order to achieve the step of 0.5 μm or less, it is also found that when forming the magnet insertion holes by thermal cutting, it is important to perform the cutting process by irradiating the heat beam used for cutting at an angle of 1 to 5° toward the hole side to be cut off with respect to the perpendicular line of the steel sheet surface, as shown in FIG. 2.

[0030] In the present invention, the thermal beam used in the thermal cutting process for cutting steel plates may be a laser beam, an electron beam, a plasma beam, or gas cutting, but hereinafter, the present invention will be described using an example in which laser cutting is used as the thermal cutting process.

[0031] The experiments that led to the development of the present invention will now be described. Rotor core materials having the shape shown in Figure 1 were manufactured using electrical steel sheet with a thickness of 0.20 mm, containing 0.0015 mass% C, 3.7 mass% Si, 0.5 mass% Mn, 1.0 mass% Al, and 0.002 mass% S, with the remainder being Fe and unavoidable impurities, by the following five methods. Method 1: Punching using a die (clearance: 5% of plate thickness) Method 2: The cut surface of the rotor core material obtained in Method 1 is smoothed by mechanical polishing. Method 3: Treat the cut surface of the rotor core material obtained in Method 1 with a ferric chloride solution (45 Baume, liquid temperature 45°C) for 10 seconds. Method 4: Laser cutting (single mode fiber laser, power: 300W, scanning speed: 10m / min, laser beam inclination angle θ=0°) Method 5: Laser cutting (single mode fiber laser, power: 300W, scanning speed: 10m / min, laser beam inclination angle θ=2°) (The inclination angle θ of the laser beam in the above methods 4 and 5 refers to the inclination angle of the laser beam from the perpendicular line of the steel plate surface toward the hole side to be cut off, as shown in FIG. 2.)

[0032] Next, a micro fatigue test piece having the shape shown in FIG. 3 (width of parallel part: 1.0 mm) was cut out from the bridge part (part A in FIG. 1) of the rotor core material and subjected to a fatigue test. At this time, the arithmetic mean roughness Ra of the cut surface (part C) of the parallel part, which is the laser cut surface, was measured in accordance with JIS B 0601-2001. The fatigue test was performed under the conditions of tension-tension (pulsating), stress ratio: 0.1, and frequency: 20 Hz, and the fatigue test was performed for 10 7 The maximum stress at which no fracture occurred even after repeated cycles was defined as the fatigue strength. The results are shown in Table 1.

[0033] [Table 1]

[0034] From Table 1, we can see the following: A comparison of Method 1 and Method 2 shows that mechanical polishing improves fatigue strength, and a comparison of Method 2 and Method 3 shows that chemical polishing further improves fatigue strength. This is thought to be because mechanical and chemical polishing reduce the surface roughness Ra of the punched cut surface, mitigating stress concentration. On the other hand, when laser cutting was performed using method 4 (tilt angle θ: 0°), the surface roughness Ra was at the same level as method 2, but the fatigue strength was not as good as that of method 2. However, method 5, in which the tilt angle θ was set to 2°, showed the highest fatigue strength among methods 1 to 5, even though the surface roughness Ra was at the same level as methods 2 and 4.

[0035] In order to investigate the cause of this, a more detailed investigation was carried out on the cut surface of the test piece. Specifically, the cut surface of the parallel part of the fatigue test piece (part C in Fig. 3) was embedded in a resin mold, and the cut surface was observed using an optical microscope. Specifically, as shown in Fig. 4, the test piece was embedded in a resin mold, and a cross section perpendicular to the cut surface was observed. In the observation surface of the embedded sample, the end corresponding to the cut surface was observed in the plate thickness direction, and the steps occurring at the grain boundaries were measured at more than 30 points. As a result, the maximum step of the test piece obtained by method 4 was more than 0.5 μm, while the maximum step of the test piece obtained by method 5 was 0.5 μm or less. From this result, it became clear that simply reducing the surface roughness of the cut surface is insufficient to improve fatigue strength, and that a rotor core with unprecedented high fatigue strength can be obtained only by further reducing the steps at the grain boundaries present on the cut surface.

[0036] Here, the mechanism by which the step at the grain boundary can be reduced by performing laser cutting with the laser beam tilt angle θ in the range of 1 to 5° is not fully understood at present, but the inventors believe it to be as follows: Multiple physical phenomena, namely melting of the steel plate by laser irradiation, removal of the molten part by the assist gas, and solidification of the molten part, affect each other in a complex manner. Therefore, by setting the angle at which the laser is irradiated to the steel plate at a specific angle rather than perpendicular to the plate, conditions are met that do not create steps at the discontinuous boundaries known as grain boundaries, improving the quality of the cut surface. The present invention was developed based on the above novel findings.

[0037] Here, there is no particular restriction on the type of laser used to form the magnet insertion hole, and it is sufficient to use a commonly used CO2 laser, fiber laser, etc. However, in order to control the step at the grain boundary on the cut surface to 0.5 μm or less, a continuous laser is preferable to a pulsed laser, since it can perform continuous and uniform processing along the processing surface.

[0038] In addition, the laser output and scanning speed are not particularly limited as long as they are conditions that can suppress the generation of dross and excessive sputtering. In the laser cutting process of the present invention, it is preferable to blow an assist gas in order to blow away the molten metal and prevent dross adhesion. There is no limit to the type of gas to be blown, and compressed air, N2, Ar gas, etc. can be used.

[0039] Next, the steel sheet used in the rotor core of the present invention is preferably a non-oriented electrical steel sheet having the following chemical composition. C: 0.0005 to 0.01 mass% Since C is an element that causes magnetic aging and deteriorates the magnetic properties of the product sheet, it is desirable to reduce it as much as possible, and in the present invention, it is preferable to limit it to 0.01 mass% or less. However, since an extreme reduction in C leads to an increase in refining costs, the lower limit is set to 0.0005 mass%, and more preferably, it is in the range of 0.0010 to 0.0040 mass%.

[0040] Si:7mass% or less Since Si is an element that increases the resistivity of steel and reduces iron loss, it is an effective element for reducing motor loss. It is also an effective element for increasing the strength of steel. In order to obtain the above effects, it is preferable that Si is contained in an amount of 0.5 mass% or more. However, the addition of more than 7 mass% not only reduces the magnetic flux density, but also hardens the steel, making it difficult to reduce the properties of the cut surface, particularly the steps at the grain boundaries present on the cut surface, when manufacturing a core material by machining such as punching. It is also undesirable because it increases the cost of raw materials. Therefore, it is preferable to limit Si to 7 mass% or less. It is more preferable to limit it to a range of 2.5 to 6.5 mass%, and even more preferable to limit it to a range of 3.5 to 6.5 mass%.

[0041] Mn: 0.05 to 3 mass% Like Si, Mn is an element that is effective in increasing the resistivity of steel to reduce iron loss and increase the strength of steel. It is also an element that improves hot workability. In order to obtain the above effects, it is preferable to contain 0.05 mass% or more. However, if it exceeds 3 mass%, it will cause a decrease in magnetic flux density, as well as harden the steel, causing a decrease in workability, and an increase in raw material costs. Therefore, Mn is preferably in the range of 0.05 to 3 mass%, and more preferably in the range of 0.06 to 1.5 mass%.

[0042] Al:3mass% or less Like Si, Al is an element that is effective in increasing the resistivity of steel to reduce iron loss and increase the strength of steel. To obtain the above effects, it is desirable to contain 0.0010 mass% or more. However, if it exceeds 3 mass%, it will cause a decrease in magnetic flux density, as well as harden the steel, causing a decrease in workability, and an increase in raw material costs, so it is preferable to limit it to 3 mass% or less. More preferably, it is in the range of 0.1 to 1.5 mass%.

[0043] The steel sheet used in the present invention contains the balance of Fe and unavoidable impurities other than the above-mentioned components, but may contain the following components as necessary. P: 0.001 to 0.1 mass% P has the effect of increasing the strength of steel and improving punching workability. In addition, P segregates at grain boundaries and has the effect of lowering the melting point of the grain boundaries and the steel in their vicinity during laser cutting, and is effective in reducing the step at the grain boundaries, so it is preferable to add 0.001 mass% or more. However, if it exceeds 0.1 mass%, the steel becomes too hard, making it difficult to roll, and inviting an increase in raw material costs. Therefore, when P is added, it is preferable to set the upper limit at 0.1 mass%. More preferably, it is in the range of 0.02 to 0.08 mass%.

[0044] S: 0.01mass% or less S is an element contained as an unavoidable impurity, but it segregates at the grain boundaries and has the effect of lowering the melting point of the grain boundaries and the steel in their vicinity during laser cutting, and is effective in reducing the step of the grain boundaries. However, if it exceeds 0.01 mass%, it forms precipitates with Mn and the like due to the heating associated with the laser cutting process, which leads to deterioration of the magnetic properties, so the upper limit is preferably 0.01 mass%. More preferably, it is 0.0020 mass% or less.

[0045] Sn:0.001~0.1mass%, Sb:0.001~0.1mass% Sn and Sb have the effect of lowering the melting point of the grain boundary and the steel in its vicinity during laser cutting by segregating at the grain boundary, and are effective in reducing the step of the grain boundary, so it is preferable to contain 0.001 mass% or more of each. However, if it exceeds 0.1 mass%, the rolling property deteriorates and the raw material cost increases, so the upper limit is preferably set to 0.1 mass%. More preferably, each is in the range of 0.02 to 0.08 mass%.

[0046] Ca:0.0002~0.005mass%, Mg:0.0002~0.005mass% Ca and Mg form stable sulfides and have the effect of improving the grain growth of the base steel sheet, so it is preferable to contain 0.0002 mass% or more of each. However, if the content exceeds 0.005 mass%, the above effect becomes saturated, so the upper limit is preferably set to 0.005 mass%. More preferably, each is in the range of 0.001 to 0.004 mass%.

[0047] Next, an object to which the laser cutting process of the present invention is applied will be described. The non-oriented electrical steel sheet used in the present invention preferably has a Si concentration gradient of 1 mass% or more in the sheet thickness direction. Since the eddy current loss of the steel sheet is concentrated in the surface layer of the sheet thickness due to the skin effect, increasing the Si concentration in the surface layer of the sheet thickness to increase the resistivity is effective in reducing the eddy current loss. In order to fully obtain this effect, it is preferable that the Si concentration difference between the surface layer and the center of the steel sheet is 1 mass% or more (the surface layer is 1 mass% or more higher than the center). Here, the above-mentioned Si concentration difference refers to the difference between the average Si concentration of the surface layer on the front and back and the Si concentration in the center when the steel sheet is divided into three in the sheet thickness direction, with the layers from the steel sheet surface to 1 / 3 of the sheet thickness on the front and back being the surface layer, and the layer sandwiched between them and the layer at 1 / 3 of the sheet thickness in the center of the sheet thickness being the surface layer. The Si concentration difference may be measured by measuring the Si concentration distribution in the cross section of the steel sheet by EPMA, or by wet analyzing the Si concentration of the steel sheet across its entire thickness and of the remaining 1 / 3 of the sheet thickness after dissolving and removing 1 / 3 of the sheet thickness from both sides of the steel sheet by chemical polishing or the like, and determining the difference therebetween.

[0048] Although electrical steel sheets having a high-Si layer on the surface have excellent magnetic properties such as iron loss in the high frequency range, they are difficult to control the properties of the cut surface by mechanical processing such as punching, etc. Therefore, it is extremely effective to apply the laser cutting process of the present invention to electrical steel sheets having a high-Si layer on the surface.

[0049] From the viewpoint of improving motor efficiency, it is effective to reduce the gap between the outer diameter of the rotor core and the inner diameter of the stator core when the motor is assembled. However, in the conventional punching process, some additional processing is required on the outer peripheral surface of the rotor core to smooth the cut surface, so it is difficult to reduce the gap. On the other hand, when the laser cutting process of the present invention is applied, the outer peripheral surface of the rotor core can be made extremely smooth with little unevenness. As a result, when the laser cutting process of the present invention is applied, it is possible to make the shortest distance between the outer diameter of the rotor core and the inner diameter of the stator core 0.30 mm or less, which can greatly contribute to improving motor efficiency. In principle, it is possible to manufacture a motor with an unprecedented narrow air gap as long as it is equal to or larger than the kerf width during laser cutting.

[0050] In manufacturing a rotor core, it is most effective to apply the laser cutting process of the present invention to the part where the centrifugal force is most concentrated when the rotor core rotates. However, by applying the laser cutting process to the outer periphery of the rotor core as well, the fatigue strength of the rotor core can be increased more reliably.

[0051] Furthermore, the laser cutting process of the present invention can be applied not only to the formation of magnet insertion holes, but also to the formation of cooling holes through which coolant flows to cool the rotor core, which is subject to stress concentration due to centrifugal force, just like the magnet insertion holes. Therefore, in the present invention, it is not necessary for permanent magnets to be inserted into all of the holes opened by the laser cutting process. In addition, it is sufficient for the permanent magnets to be inserted into a portion of the opening area of ​​the magnet insertion holes, and they do not need to occupy the entire area.

[0052] As mentioned above, the above description has been given with an example of cutting using a laser beam as a thermal beam (laser cutting), but thermal cutting using an electron beam, plasma beam, gas cutting, etc., other than a laser beam, may also be used. However, from the viewpoints of reducing manufacturing costs, improving productivity, and suppressing capital investment, laser cutting is most preferable. EXAMPLES

[0053] Steel having the composition shown in Table 2, with the remainder consisting of Fe and unavoidable impurities, was melted by a commonly known refining process, and was continuously cast to obtain a steel material (slab), which was then hot-rolled to obtain a hot-rolled sheet with a thickness of 2.3 mm. This hot-rolled sheet was then annealed at 1000°C for 10 s, pickled, and cold-rolled to obtain a cold-rolled sheet with the final thickness shown in Table 2. The cold-rolled sheet was then subjected to finish annealing in an atmosphere of 20 vol% H2-80 vol% N2, where it was held for 10 s at various temperatures shown in Table 2. Thereafter, an insulating coating of an organic / inorganic mixture was formed on the surface of the steel sheet to obtain a non-oriented electrical steel sheet (product sheet).

[0054] Using the product plate thus obtained as the material, a steel plate (rotor core material) having the shape shown in Figure 1 was processed by various methods as shown in Table 2. Then, a fatigue test specimen having the shape shown in Figure 3 was cut out from part A (see Figure 1) of the rotor core material and subjected to a fatigue test. At this time, the step at the grain boundary present on the laser cut surface (part C, see Figure 3) of the parallel part of the test specimen was measured in the same manner as in the above-mentioned experiment. The fatigue test was also performed under the conditions of tension-tension (pulsating), stress ratio: 0.1, and frequency: 20 Hz, and the fatigue test was performed for 10 7 The maximum stress at which no fracture occurred even after repeated cycles was defined as the fatigue strength.

[0055] The results of the above measurements, together with the steel components and manufacturing conditions, are shown in Table 2. From these results, it can be seen that high fatigue strength is obtained when the maximum difference in grain boundary height present on the laser cut surface is 0.5 μm or less, and this difference in height is obtained when the inclination angle θ is set in the range of 1 to 5° in the laser cutting process. On the other hand, it is clear that with laser cutting and punching processes that do not meet the above conditions, the difference in grain boundary height cannot be made 0.5 μm or less, and high fatigue strength is not obtained. Among them, in the invention examples in which the inclination angle θ is set in the range of 3 to 5°, the step of the crystal grain boundary present on the laser cut surface is 0.33 μm or less.

[0056] [Table 2] EXAMPLES

[0057] A steel containing 0.01 mass% C, 2 mass% Si, 0.03 mass% Mn, 0.005 mass% Al, with the balance being Fe and unavoidable impurities, was melted by a commonly known refining process and continuously cast into a steel material (slab). The slab was then hot-rolled to a hot-rolled sheet having a thickness of 2.0 mm. The hot-rolled sheet was then annealed at 1000°C for 10 s, pickled, and cold-rolled to a cold-rolled sheet having a final thickness of 0.1 mm. The cold-rolled sheet was then heat-treated at 1200°C in a mixed gas of silicon tetrachloride and N2 to increase the Si concentration in the steel sheet surface layer. At this time, various non-oriented electrical steel sheets (product sheets) with different Si concentration distributions were manufactured by adjusting the concentration of silicon tetrachloride and the holding time.

[0058] The Si concentration distribution and C content of the product plate thus obtained were measured. As in Example 1, rotor core material having the shape shown in FIG. 1 was taken from the product plate under laser cutting conditions of output: 200 W, scanning speed: 30 m / min, and inclination angle θ: 2°, and fatigue test pieces were cut out from the bridge portion (part A) and subjected to fatigue testing. At this time, the grain boundary steps present on the laser cut surface (part C, see FIG. 3) of the parallel portion of the test piece were measured. The fatigue test was performed under the conditions of tension-tension (pulsating), stress ratio: 0.1, and frequency: 20 Hz, and the fatigue test was performed for 10 7 The maximum stress at which no fracture occurred even after repeated cycles was defined as the fatigue strength.

[0059] The results of the measurements are shown in Table 3. These results show that the fatigue strength of steel plates that have been siliconized is greatly improved. In particular, steel plates with a difference in Si concentration of 1 mass% or more between the surface layer and the center of the plate have higher fatigue strength than steel plates with a uniform Si concentration in the plate thickness direction, even if the average Si content is the same.

[0060] [Table 3] [Industrial Applicability]

[0061] The technology of the present invention is not limited to rotor cores of IPM motors in which centrifugal force is applied to magnets, but can also be applied to rotor cores of synchronous reluctance motors and the like that do not have magnet insertion holes, and to fields in which magnetic circuits are configured to improve motor characteristics.

Claims

1. A rotor core formed by laminating steel plates obtained by cutting a material steel plate and processing the steel plate into an outer peripheral shape of the rotor core, The steel plate has a plurality of holes formed therein by thermal cutting, and A rotor core characterized in that the maximum difference in level at the grain boundaries present on the cut surface of the hole is 0.33 μm or less.

2. The material steel sheet contains C: 0.0005 to 0.01 mass%, Si: 7 mass% or less, Mn: 0.05 to 3 mass%, and Al: 3 mass% or less, and optionally contains at least one selected from P: 0.001 to 0.1 mass%, S: 0.01 mass% or less, Sn: 0.001 to 0.1 mass%, Sb: 0.001 to 0.1 mass%, Ca: 0.0002 to 0.005 mass%, and Mg: 0.0002 to 0.005%. The rotor core according to claim 1, characterized in that it is a non-oriented electromagnetic steel sheet consisting of Fe and unavoidable impurities.

3. The rotor core according to claim 1, characterized in that, when the surface layer portion of the material steel plate is from the front and back surfaces of the steel plate to 1 / 3 of the plate thickness, and the center portion is from the steel plate surface to the inside of 1 / 3 of the plate thickness, the average Si content of the front and back surfaces of the surface layer portion is 1 mass% or more higher than that of the center portion.

4. The rotor core according to claim 2, characterized in that, when the surface layer portion of the material steel plate is from the front and back surfaces of the steel plate to 1 / 3 of the plate thickness, and the center portion is from the steel plate surface to the inside of 1 / 3 of the plate thickness, the average Si content of the front and back surfaces of the surface layer portion is 1 mass% or more higher than that of the center portion.

5. The rotor core according to any one of claims 1 to 4, characterized in that the thermal cutting process is a laser cutting process.

6. 5. The rotor core according to claim 1, wherein the outer periphery of the steel plate processed into the shape of the rotor core is thermally cut.

7. 6. The rotor core according to claim 5, wherein the outer periphery of the steel plate processed into the shape of the rotor core is thermally cut.

8. 7. The rotor core according to claim 6, wherein the thermal cutting of the outer periphery is performed by laser cutting.

9. 8. The rotor core according to claim 7, wherein the thermal cutting of the outer periphery is performed by laser cutting.

10. 5. The rotor core according to claim 1, wherein permanent magnets are inserted into some or all of the holes.

11. 6. The rotor core according to claim 5, wherein permanent magnets are inserted into some or all of the holes.

12. A manufacturing method of a rotor core, comprising the steps of forming a plurality of holes by thermal cutting in a rotor core-shaped steel plate obtained from a base steel plate having the composition according to claim 2, and then laminating the steel plates to assemble the rotor core, In the thermal cutting process, the heat beam is irradiated at an angle of 3 to 5 degrees toward the hole to be cut off with respect to the perpendicular line to the steel plate surface, thereby making the maximum step value of the grain boundary present on the cut surface 0.5 μm or less. This is a manufacturing method for a rotor core.

13. The method for manufacturing a rotor core as described in claim 12, characterized in that, when the surface layer portion of the material steel plate is from the front and back surfaces of the steel plate to 1 / 3 of the plate thickness, and the center portion is from the steel plate surface to the inside of 1 / 3 of the plate thickness, the average Si content of the front and back surfaces of the surface layer portion is 1 mass% or more higher than that of the center portion.

14. 14. The method for manufacturing a rotor core according to claim 12 or 13, characterized in that the thermal cutting process is a laser cutting process.

15. 14. The method for manufacturing a rotor core according to claim 12 or 13, further comprising the step of thermally cutting an outer periphery of the steel plate processed into the shape of the rotor core.

16. The method for manufacturing a rotor core according to claim 14, further comprising the step of thermally cutting an outer periphery of the steel plate processed into the shape of the rotor core.

17. The manufacturing method of a rotor core according to claim 15, characterized in that the thermal cutting of the outer periphery is a laser cutting process.

18. The manufacturing method of a rotor core according to claim 16, characterized in that the thermal cutting of the outer periphery is a laser cutting process.

19. A motor having a rotor core and a stator core, the rotor core being formed using the core according to any one of claims 1 to 4, A motor characterized in that the shortest distance between the outer diameter of the rotor core and the inner diameter of the stator core is 0.30 mm or less.

20. A motor having a rotor core and a stator core, the rotor core being formed using the core according to claim 5, A motor characterized in that the shortest distance between the outer diameter of the rotor core and the inner diameter of the stator core is 0.30 mm or less.

Citation Information

Patent Citations

  • Silicon steel sheet reduced in iron loss

    JP1989068444A

  • Laser beam cutting machine

    JP1991180294A

  • Motor

    JP2002044920A

  • Rotor of magnetic steel sheet having low iron loss, rotor manufacturing method, and laser-peening method and laser-peening device

    JP2005124386A

  • Method for cutting-off steel plate by laser beam

    JP2006231363A